The prevalence of Cyclospora cayetanensis in water: a systematic review and meta-analysis. (10th December 2022) - Naganathan, Thivya; O'Connor, Annette; Sargeant, Jan M.; Shapiro, Karen; Totton, Sarah; Winder, Charlotte; Greer, Amy L.
Abstract: Cyclospora cayetanensis is an emerging food- and waterborne pathogen that causes cyclosporiasis, a gastrointestinal disease in humans. The parasite is endemic in tropical and subtropical regions; however, its prevalence is largely dependent on environmental factors, such as climate and rainfall patterns. The objective of this paper was to conduct a systematic review and meta-analysis to determine the prevalence of C. cayetanensis in water and to determine if geography, water source and other variables influence this prevalence. A literature search was performed using search terms relating to water and C. cayetanensis in MEDLINE ®, CAB Direct, Food Science and Technology Abstracts, Agricola databases and Environmental Science Index. Observational studies published in English after 1979 were eligible. Screening, data extraction and risk-of-bias assessment were performed independently by two reviewers. A multi-level random-effects meta-analysis was completed to determine the prevalence of C. cayetanensis in water and subgroup meta-analyses were performed to explore between-study heterogeneity. The search identified 828 unique articles, and after the screening, 33 articles were included in the review. The pooled prevalence of C. cayetanensis in water was 6.90% [95% confidence interval (CI) 2.25%–13.05%, I 2 = 84.38%]. Subgroup meta-analyses revealed significant differences in the prevalence between continents. Additionally, laboratory methods between studies were highly variable and these findings highlight the need for further environmental research on C. cayetanensis in water using detection methods that include PCR and sequencing to accurately identify the organism. The results of this study can be used to help assess the risk of waterborne cyclosporiasis.